Abdominal cocoon accompanied by multiple peritoneal loose body - Cheng, Yongyuan (Medicine (Baltimore), 2017)
RATIONALE: Abdominal cocoon and peritoneal loose body are both rare abdominal diseases. PATIENT CONCERNS: The patient reported in this case was a 47-year-old man who suffered from abdominal pain and distension for 3 days. DIAGNOSIS: X-ray, computed tomography, and magnetic resonance imaging revealed multiple peritoneal loose body and small bowel obstruction, characterized by a total encapsulation of the small bowel with a fibrous membrane. INTERVENTIONS: The patient underwent surgical treatment and exploratory laparotomy confirmed the diagnosis of abdominal cocoon. OUTCOMES: Histopathological examination of pelvic nodules confirmed peritoneal loose body. LESSONS: To our knowledge, the herein reported case is the first abdominal cocoon that was accompanied by multiple peritoneal loose body.